2015
DOI: 10.1037/edu0000036
|View full text |Cite
|
Sign up to set email alerts
|

How readability and topic incidence relate to performance on mathematics story problems in computer-based curricula.

Abstract: Solving mathematics story problems requires text comprehension skills. However, previous studies have found few connections between traditional measures of text readability and performance on story problems. We hypothesized that recently developed measures of readability and topic incidence measured by text-mining tools may illuminate associations between text difficulty and problem-solving measures. We used data from 3,216 middle and high school students from 10 schools using the Cognitive Tutor Algebra progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 93 publications
0
21
0
Order By: Relevance
“…In prior work (Walkington, Clinton, Ritter, et al, 2015), we examined 151 story problems from a widely used Algebra I curriculum, Cognitive Tutor Algebra , as well as a set of 60 algebra story problems from a middle school tutoring software, MATHia . We entered the text of the story problems into two text analysis programs—Coh-Metrix and LIWC.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In prior work (Walkington, Clinton, Ritter, et al, 2015), we examined 151 story problems from a widely used Algebra I curriculum, Cognitive Tutor Algebra , as well as a set of 60 algebra story problems from a middle school tutoring software, MATHia . We entered the text of the story problems into two text analysis programs—Coh-Metrix and LIWC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We also examined performance on the fourth- and eighth-grade released items on the NAEP and TIMSS (Walkington, Clinton, Shivraj, & Yovanoff, 2015). These data sets simply gave an overall accuracy statistic for each problem averaged for every student who took the test.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Boonen, van Wesel, Jolles, and van der Schoot (2014) indicated that conceptual understanding through reading the context of mathematical word problems plays an import role in problem-solving. However, one of the problem-solving skills children have been found to have difficulties with is the ability to comprehend the conception of a mathematical word problem (Schoppek & Tulis, 2010;Walkington, Clinton, Ritter, & Nathan, 2015). As there is a strong relationship between reading comprehension and solving mathematical word problems, how to improve these skills while learning mathematical skills has become an important issue in achieving effective, meaningful learning through problem-solving (Lee & Chen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have indicated that employing CAAF to provide personalized teaching and remedial materials is essential to improving students' learning behaviors (de-Marcos, Garcia-Lopez, & Garcia-Cabot, 2016;Hsiao et al, 2014) and academic achievement in different disciplines (Hsiao et al, 2015;Hsiao, Chang, Lin, & Wang, 2016;Walkington et al, 2015;Yung & Paas, 2015). From a practical point of view, the mathematical ability of each student may contribute to the interpretation of individual differences in problem-solving.…”
Section: Introductionmentioning
confidence: 99%
“…Teachers and researchers can use information about the underlying skill model to determine if skills differ in important ways, such as determining which skills are more likely to be associated with disengagement (e.g. [1]) or negative affect [11], and to study how hint requests and other metacognitive behaviors vary between different skills [24]. Skill models can also help to inform teachers' assessments of student learning and performance, and identify areas where students may need additional practice or scaffolding in order to succeed.…”
Section: Introductionmentioning
confidence: 99%